Recent advances in catalytic asymmetric synthesis - Garg, Ashna; Rendina, Dominick; Bendale, Hersh; Akiyama, Takahiko; Ojima, Iwao (Frontiers in Chemistry, 2024)
Asymmetric catalysis stands at the forefront of modern chemistry, serving as a cornerstone for the efficient creation of enantiopure chiral molecules characterized by their high selectivity. In this review, we delve into the realm of asymmetric catalytic reactions, which spans various methodologies, each contributing to the broader landscape of the enantioselective synthesis of chiral molecules. Transition metals play a central role as catalysts for a wide range of transformations with chiral ligands such as phosphines, N-heterocyclic carbenes (NHCs), etc., facilitating the formation of chiral C-C and C-X bonds, enabling precise control over stereochemistry. Enantioselective photocatalytic reactions leverage the power of light as a driving force for the synthesis of chiral molecules. Asymmetric electrocatalysis has emerged as a sustainable approach, being both atom-efficient and environmentally friendly, while offering a versatile toolkit for enantioselective reductions and oxidations. Biocatalysis relies on nature’s most efficient catalysts, i.e., enzymes, to provide exquisite selectivity, as well as a high tolerance for diverse functional groups under mild conditions. Thus, enzymatic optical resolution, kinetic resolution and dynamic kinetic resolution have revolutionized the production of enantiopure compounds. Enantioselective organocatalysis uses metal-free organocatalysts, consisting of modular chiral phosphorus, sulfur and nitrogen components, facilitating remarkably efficient and diverse enantioselective transformations. Additionally, unlocking traditionally unreactive C-H bonds through selective functionalization has expanded the arsenal of catalytic asymmetric synthesis, enabling the efficient and atom-economical construction of enantiopure chiral molecules. Incorporating flow chemistry into asymmetric catalysis has been transformative, as continuous flow systems provide precise control over reaction conditions, enhancing the efficiency and facilitating optimization. Researchers are increasingly adopting hybrid approaches that combine multiple strategies synergistically to tackle complex synthetic challenges. This convergence holds great promise, propelling the field of asymmetric catalysis forward and facilitating the efficient construction of complex molecules in enantiopure form. As these methodologies evolve and complement one another, they push the boundaries of what can be accomplished in catalytic asymmetric synthesis, leading to the discovery of novel, highly selective transformations which may lead to groundbreaking applications across various industries.